The United Kingdom against Bribery through Bribery Act 2010: Does the Act can be considered as the One of the Best Anti-Bribery Legislation in the world? - Diastama Anggita Ramadhan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
AbstractBritain as one of the developed countries in the world has a fairly ancient law related to the eradication of corruption. Corruption as a modern crime requires a fairly revolutionary reform of the law to force Britain to make a new law. This new law will be more flexible in accordance with the common law school of law adopted by the UK. This article aims to assess whether the new law related to corruption eradication made by the UK can become a reliable law. This article will discuss about the new features in fighting corruption in the UK as well as some international aspects that allow legal subjects outside the British nationality to commit acts of corruption in the UK.